Rhodanine scaffold: A review of antidiabetic potential and structure-activity relationships (SAR) - Ahmad Khairul Daniel bin Ahmad Kamar; Lim Ju Yin; Chin Tze Liang; Gan Tjin Fung; Vasudeva Rao Avupati (Elsevier, 2022)
Diabetes is a chronic medical condition due to the lack of insulin or ineffective use of insulin. In recent years, diabetes has become one of the rapidly growing chronic diseases, and it has caused a burden on the individual and the economy. Rhodanine has been identified as an important scaffold in drug discovery because of its wide range of biological properties including antidiabetic. A number of studies have been reported regarding the activity of rhodanine-based compounds in the treatment of diabetes mellitus and its complications. This review aimed to explore the antidiabetic activity of rhodanine-based compounds and their structure-activity relationship (SAR) based on studies that have been reported. Our study discovered several studies about the compounds' biological screening against a variety of targets, including aldose reductase, α-glucosidase, α-amylase, PPAR-γ and PTPT1B. Some compounds mentioned are also tested in vivo in living organisms. This review offers a resource for future antidiabetic drug development, as many of the hit compounds listed exhibited good antidiabetic properties.